1996
DOI: 10.1051/alr:1996016
|View full text |Cite
|
Sign up to set email alerts
|

Virulence factors ofVibrioP1, the causative agent of brown ring disease in the Manila clam,Ruditapes philippinarum

Abstract: ResumenSeveral virulence factors involved in the potential pathogenic capacity of Vibrio Pl, the causative agent of brown ring disease (BRD) affecting cultured Manila clam adults (Ruditupes philippinarum), have been evaluated in comparison with other strains of several Vibrio species isolated from diseased clams. The importance of bacterial ceIl surface associated properties as virulence factors has been studied considering both non-specific and specific bacterial adhesion to clams. Vihrio Pl showed moderate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 50 publications
2
30
1
1
Order By: Relevance
“…A wide range of enzymatic activities were demonstrated in the ECPs but it was not possible to link one specific enzymatic pattern with the toxic activity. Though most of these exoenzymes a r e considered a s putative virulence factors by some authors (Borrego et al 1996), their presence in culture supernatants could not b e related to virulence in the present study.…”
Section: In Vitro Assayscontrasting
confidence: 72%
“…A wide range of enzymatic activities were demonstrated in the ECPs but it was not possible to link one specific enzymatic pattern with the toxic activity. Though most of these exoenzymes a r e considered a s putative virulence factors by some authors (Borrego et al 1996), their presence in culture supernatants could not b e related to virulence in the present study.…”
Section: In Vitro Assayscontrasting
confidence: 72%
“…Further, the cell wall contains smooth lipopolysaccharides that, according to Bradley (1979), play an important role in virulence by helping the penetration of pathogens into host tissues. They also allow bacteria to better resist the defense system of clams, particularly phagocytosis by hemocytes (Borrego et al 1996b). In the present study, we noted the persistence of bacteria in clams without obvious signs of weakness (clams sampled for ELISA) and found high concentrations, with severe pathological changes, in moribund clams.…”
Section: Discussionsupporting
confidence: 62%
“…), and plasmids coding for iron chelators (Horne 1982, Toranzo et al 1983, Moustafa et al 1984, Nottage & Birkbeck 1986. V. tapetis factors include hemolysins, cytotoxins, exotoxins, and plasmids (Borrego et al 1996b, Castro et al 1997. In vitro experiments have shown that V. tapetis cells are able to kill cultured fish cells and hemocytes of Ruditapes philippinarum (Borrego et al 1996b, Lane 1997.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors concluded that an important part of the pathogenicity of this bacteria is attributable to Vibrio aesturianus extracellular products. Vibrio tapetis ECP have been shown to induce vacuolization, rounding, shrinking, detaching, and finally, destruction of fish cultured cells (Borrego et al, 1996a) and to inhibit adhesion properties of R. philippinarum haemocytes (Choquet, 2004). The existence of deleterious ECP effects by V. tapetis supports the hypothesis that filtration activity could be inhibited by one or more factors produced by this bacterium.…”
Section: Discussionmentioning
confidence: 99%